Планування інформаційно-рекламної діяльності стоматологічних послуг у соціальних мережах - Стадник, Олена; Білущак, Тетяна (Видавництво Львівської політехніки, 2020)
In the study, for effective informational and advertising support of a company in social networks, it is necessary to correctly plan tasks to achieve your goal. It has been suggested that this is best done using the “goal tree”.
Keywords: соціальні мережі; реклама; інформаційне забезпечення; популяризація